Understanding financial inclusion in China - Zuzana Fungáčová; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
We use data from the World Bank Global Findex database for 2011 to analyze financial inclusion in China, including comparisons with the other BRICS countries. We find a high level of financial inclusion in China manifested by greater use of formal account and for-mal saving than in the other BRICS. Financial exclusion, i.e. not having a formal account, is mainly voluntary. The use of formal credit is however less frequent in China than in the other BRICS. Borrowing through family or friends is the most common way of obtaining credit in all the BRICS countries, but other channels for borrowing are not very commonly used by individuals in China. We find that higher income, better education, being a man, and being older are associated with greater use of formal accounts and formal credit in China. Income and education influence the use of alternative sources of borrowing. Overall financial inclusion does not constitute a major problem in China, but such limited use of formal credit can create a challenge for further economic development.
URN:NBN:fi:bof-201408072217
Keywords: G21; O16; P34; 330; financial inclusion; financial institutions; China